2020
DOI: 10.1371/journal.pone.0233391
|View full text |Cite
|
Sign up to set email alerts
|

Southern-style Pad Thai sauce: From traditional culinary treat to convenience food in retortable pouches

Abstract: Pad Thai, a Thai dish of stir-fried rice noodles and other ingredients, is one of the culinary heritages of Thailand. In the southern region of Thailand, Pad Thai has different characteristics from other areas because coconut milk and curry paste are used to produce a thick sauce prior to cooking. To commercially distribute this uniquely local culinary treat in a convenient form all over Thailand and other export markets, a shelf-stable sauce using heat sterilization should be developed. Retort processing tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…6c) of both gels were changed considerably during storage but lower values of all indices were noticeable in gel with lecithin. Beside a direct antioxidant activity, lecithin may be served as a barrier to separate the oil from the water-soluble prooxidants, for example metal ions and polar free-radicals (Cheenkaew et al, 2020). The residual lipid could be stabilised by the addition of lecithin to some degree, and thus, the oxidation was lowered.…”
Section: Microstructurementioning
confidence: 99%
“…6c) of both gels were changed considerably during storage but lower values of all indices were noticeable in gel with lecithin. Beside a direct antioxidant activity, lecithin may be served as a barrier to separate the oil from the water-soluble prooxidants, for example metal ions and polar free-radicals (Cheenkaew et al, 2020). The residual lipid could be stabilised by the addition of lecithin to some degree, and thus, the oxidation was lowered.…”
Section: Microstructurementioning
confidence: 99%
“…Our study showed that Kaeng‐Tai‐Pla‐Haeng had an A w below 0.85, which is in the range required by TCPS (2018). However, with its A w , this sample may easily be spoiled by mould; it is in a suitable condition for mould growth (Cheenkaew et al ., 2020). The inorganic contaminants, including Pb, As, Cd, and Hg, were also analysed in this study to confirm that this product is acceptable according to the standard TCPS (2018).…”
Section: Resultsmentioning
confidence: 99%
“…Kaeng‐tai‐pla‐haeng is cooked and processed by heating the mixture of all curry ingredients under continuous stirring until water activity ( A w ) has reached approximately 0.85 or lower (Choopan et al ., 2021). However, this product is highly susceptible to contamination by fungi of various genera, among which Penicillium and Aspergillus are the most commonly found fungi (Cheenkaew et al ., 2020). Fungal spoilage can cause the deterioration of the odour, flavour, or texture of food ingredients, and strongly negative health impacts are possible from mycotoxins (Guimarães et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…and salt in a ratio of 2-3:1 (fish: salt) fermented at 25 o C for 12−18 months. The fermentation results are then drained and allowed to stand for 2−12 weeks before packaging [18,46,47]. In Vietnam, fish sauce (Nuoc-Mam) is processed using Stolephorus commersonii and salt in a ratio of 3:1-2 (Fish: salt) fermented for 9-12 months or more in sealed barrels [5].…”
Section: Anchovy Fish Saucementioning
confidence: 99%